Analysis of the educational policymaking process in Georgia: a case of House Bill (HB) 247 (amended1999) on bullying in schools - Dzimiri, Wonderful (Midlands State University, 2016)
This study analysed the educational policy making process in the state of Georgia in respect of House Bill 247 (amended), which entailed considering the events, social pressures and other indicators that pushed the bullying problem on the policy agenda. Of particular focus was identifying the problem that House Bill 247 sought to address, how this problem was identified and defined, indicators of the problem s existence, and the nature of actors and events that pushed this problem to prominence (agenda status) and inherent contradictions, if any, among actors. Employing the case study strategy, data were collected through document or textual analysis complemented by interviews with purposively selected key participants in and outside the Georgia legislature. Findings indicated that HB 247 educational policymaking in Georgia took an irrational process whereby politicians drafted policy drafts and shelved them until events that heightened public mood characterised by public debates for or against, judicial trials pushed the issue to agenda status. These events and attendant public mood opened a policy window through which to push the bullying issue onto agenda status. Coupling of the proposal to existing legislation was a political strategy of enlisting support for the bill from legislators on both political divides, which ensured easy sailing on the legislative floor. Conclusively, the policy making process characterizing the was not as neat a rational process.